The Poetic Power of Place Comparative Perspectives on Austronesian Ideas of Locality - J. Fox, James (ANU Press, 2006)
This collection of papers is the fourth in a series of volumes on the work of the Comparative Austronesian Project. Each paper describes a specific Austronesian locality and offers an ethnographic account of the way in which social knowledge is vested, maintained and transformed in a particular landscape. The intention of the volume is to consider common patterns in the representation of place among Austronesian-speaking populations.